Whole of Government: An Effective Strategy for Ensuring Child Support Post-Religious Court Rulings - Istiqomah Sinaga; Asmuni Asmuni; Dhiauddin Tanjung (Nurani)
Although parental responsibility in providing child support was determined by a religious court, many parents have simply ignored the specific level of obligation until such time that any debt had been declared satisfied on behalf of indebtedness once accrued — i.e., when they are no longer able to fulfill weekly financial 'honey-do lists'. Religious courts have no binding force, and cannot enforce him fulfill his obligations as a parent. This is largely because religious court decisions do not carry the force of law and cannot be enforced against those who disregard them. But the fact that one can bear to pay child support after a court decision should not be neglected and effective mechanisms must help each kid, especially those divorced. This research aims to evaluate how well the 'Whole of Government Response' strategy works in securing post-divorce child support, using a qualitative, normative juridical approach based on secondary data. The study results conclude that a "Whole of Government" approach is feasible and may offer substantial potential to address problems associated with neglected child support post-divorce. Co-responsibility of ministries and agencies to carry out child support. This is a very important thing, considering that the life of children has now become more popular by government attention also in RPJMN 2020-2024 there are policies on improvements for unsurpassed quality of living for good to implement based multi dimensional multicultural sustainability and natural geography. This research aims to evaluate how well the 'Whole of Government Response' strategy works in securing post-divorce child support.